(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The change in stored drinking water quality in containers calls for concern due to possible biofilm build-up by bacteria that find their way into water. The study aimed to determine the biofilm and virulent properties of associated bacteria. Thus, thirty water samples from some homes were collected, stored, and analyzed using spread and streaking techniques to isolate characteristic bacterial colonies on standard media. A total of 29 bacterial isolates belonging to five genera were identified molecularly. The bacteria isolates, namely: Bacillus flexus, Chryseobacterium aquifrigidense, Providencia stuartii, Alcaligene faecalis, and Providencia rustigianii were obtained. The bacterial isolates with their percentage virulent potential are as follows: Bacillus flexus 100%, Chryseobacterium aquifrigidense16.6%, Providencia stuartii 33%, Alcaligene faecalis 66% and Providencia rustigianii 33.3%. All bacterial isolates developed/expressed biofilm formation except Chryseobacterium aquifrigidense. Biofilm formation in the interior surface wall of drinking water storage containers also depended on the nature and type of storage vessel or container used in the home. The virulence factors exhibited by these potential pathogens have a a vital role in invading underlying or immune-compromised individuals. Thus, the effect of the change of stored drinking water in containers can be mitigated when individuals maintain good personal hygiene and boost their immune system to put off the potential of opportunistic pathogens recovered in this study